2016
DOI: 10.1017/s0967199416000198
|View full text |Cite
|
Sign up to set email alerts
|

Addition of granulosa cell mass to the culture medium of oocytes derived from early antral follicles increases oocyte growth, ATP content, and acetylation of H4K12

Abstract: The main aim of the present study was to examine the hypothesis that an increase in the number of granulosa cells surrounding developing bovine oocytes results in both high ATP levels and an increase in the acetylation level of H4K12 in oocytes grown in vitro. Oocyte-granulosa cell complexes (OGCs) were collected from early antral follicles (EAFs, 0.4-0.7 mm in diameter), and individually cultured on 96-well plates with or without additional granulosa cell mass that had been prepared from other OGCs. After 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The diameter, acetylation levels, and chromatin configuration are known to be useful markers of oocytes growth . Our study showed that GC‐rich FF enhanced the progression of chromatin configuration which mirrors the high ability of GC‐rich FF to support oocyte growth in vitro.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The diameter, acetylation levels, and chromatin configuration are known to be useful markers of oocytes growth . Our study showed that GC‐rich FF enhanced the progression of chromatin configuration which mirrors the high ability of GC‐rich FF to support oocyte growth in vitro.…”
Section: Discussionsupporting
confidence: 59%
“…Although factors supporting these oocyte changes have not been fully elucidated, the number of GCs surrounding the oocytes has been reported to be associated with the lipid content and histone acetylation levels. For example, when oocytes derived from EAFs were cultured in vitro, the chromatin condensed and the GC number at the end of the culture period was closely related to the lipid and ATP content and the level of acetylation in oocytes . It has been previously reported that even in the antral follicles of same size, the average number of GCs differs among donor gilts but is related to the developmental ability of the enclosed oocytes .…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported a close relationship between the number of granulosa cells and lipid and ATP content in oocytes, as well as the acetylation level of histone 4 lysine 12 (H4K12) in oocytes (Munakata et al, ). Similarly, an OGC culture system with extra granulosa cells increases ATP and lipid content as well as histone acetylation (Sugiyama et al, ). The overall improvements in granulosa cell number and oocyte content of ATP and lipids for OGCs cultured with PAG also translated to greater H4K12 acetylation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…pyruvate and lactate. Several studies have shown that the number of GCs surrounding the oocyte plays an important (and positive) role in its energy status (ATP levels) (Munakata et al 2016a, Sugiyama et al 2016. Mitochondria are essential for the normal development and viability of oocytes.…”
Section: Energy Metabolism Of Granulosa Cells and Oocytesmentioning
confidence: 99%